Potential biomarker of brain response to opioid antagonism in adolescents with eating disorders: a pilot study - Stancil, Stephani L.; Yeh, Hung-Wen; Brucks, Morgan G.; Bruce, Amanda S.; Voss, Michaela; Abdel-Rahman, Susan; Brooks, William M.; Martin, Laura E. (Frontiers in Psychiatry, 2023)
Background Eating Disorders (ED) affect up to 5% of youth and are associated with reward system alterations and compulsive behaviors. Naltrexone, an opioid antagonist, is used to treat ED behaviors such as binge eating and/or purging. The presumed mechanism of action is blockade of reward activation; however, not all patients respond, and the optimal dose is unknown. Developing a tool to detect objective drug response in the brain will facilitate drug development and therapeutic optimization. This pilot study evaluated neuroimaging as a pharmacodynamic biomarker of opioid antagonism in adolescents with ED. Methods Youth aged 13–21 with binge/purge ED completed functional magnetic resonance imaging (fMRI) pre- and post-oral naltrexone. fMRI detected blood oxygenation-level dependent (BOLD) signal at rest and during two reward probes (monetary incentive delay, MID, and passive food view, PFV) in predefined regions of interest associated with reward and inhibitory control. Effect sizes for Δ%BOLD (post-naltrexone vs. baseline) were estimated using linear mixed effects modeling. Results In 12 youth (16–21 years, 92% female), BOLD signal changes were detected following naltrexone in the nucleus accumbens during PFV (Δ%BOLD −0.08 ± 0.03; Cohen’s d −1.06, p = 0.048) and anterior cingulate cortex during MID (Δ%BOLD 0.06 ± 0.03; Cohen’s d 1.25, p = 0.086). Conclusion fMRI detected acute reward pathway modulation in this small sample of adolescents with binge/purge ED. If validated in future, larger trials, task-based Δ%BOLD detected by fMRI may serve as a pharmacodynamic biomarker of opioid antagonism to facilitate the development of novel therapeutics targeting the reward pathway, enable quantitative pharmacology trials, and inform drug dosing. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT04935931, NCT#04935931.